The Winchcombe meteorite, a unique and pristine witness from the outer solar system - King, AJ; Daly, L; Rowe, J; Bryson, JFJ; Curtis, RJ; Warren, T; Bowles, N; Sridhar, S (American Association for the Advancement of Science, 2022)
Direct links between carbonaceous chondrites and their parent bodies in the solar system are rare. The Winchcombe meteorite is the most accurately recorded carbonaceous chondrite fall. Its pre-atmospheric orbit and cosmic-ray exposure age confirm that it arrived on Earth shortly after ejection from a primitive asteroid. Recovered only hours after falling, the composition of the Winchcombe meteorite is largely unmodified by the terrestrial environment. It contains abundant hydrated silicates formed during fluid-rock reactions, and carbon- and nitrogen-bearing organic matter including soluble protein amino acids. The near-pristine hydrogen isotopic composition of the Winchcombe meteorite is comparable to the terrestrial hydrosphere, providing further evidence that volatile-rich carbonaceous asteroids played an important role in the origin of Earth’s water.